STUDI GERUSAN LOKAL AKIBAT SEDIMENTASI DI HULU BENDUNG - , Suhada Arief ([Yogyakarta] : Universitas Gadjah Mada, 2013)
By the time the water flowing in the river, a number of basic sediment (bed load) and fine (suspended load) carried with the flow. At the time the river flow is hampered due to weir the flow rate of the river bottom will be reduced, and the ability of water to carry sediment flow will be reduced as well, it leads to the deposition of sediment.The sediments will continue to increase up to the weir crest. Sediment deposition resulting in reduced counting weir height, it causes changes in the water level upstream of the weir, which high impact on changing the energy of water flowing over the weir. These changes result in changes in the energy difference between the high-energy water upstream with downstream weir. Stream flowing on the surface of the sloping weir in the supercritical state, while the flow conditions downstream of the weir is subcritical. Flow changes from supercritical to subcritical cause hydraulic jump (Raju, 1986). As a result of the hydraulic jump is often cause the waves or eddies (vortex) which can cause scouring at the base of the channel. It is therefore necessary to study the relationship between changes in high-energy (head) due to sedimentation in the weir upstream and downstream weir scour occurring. The research was conducted in the laboratory of civil engineering hydraulics using an open channel (flume) equipped with hydraulic circuits, doors and measuring tools. Theory for flow using criteria that had been developed in Irrigation Planning Standards - Building Planning Criteria KP-02, by the Public Works Departmen based on data from the United State Bureau of Reclamation (USBR), the United State Army Corps of Engineers. Local scoure theory using empirical equations that have been studied previously as Schoklitsch (1932), Veronese (1937), Jaeger (1939), Catakii (1973). Results from the research showed that the increasing sedimentation in the upstream weir resulted